PENGOLAHAN SUSU KUDA LIAR MENJADI PERMEN SUSU UNTUK PEMBERDAYAN MASYARAKAT PETERNAK DI DESA PENYARING KECAMATAN MOYO UTARA SUMBAWA NTB - Husni, Husni; Umar, Umar; Hidayatullah, Muhammad; Anugrah, Rifki; Ananda, Rizki Qori (Universitas Mataram, 2024)
Penyaring Village is one of the villages in Moyo Utara District, Sumbawa Regency, West Nusa Tenggara Province. Moyo Utara District has 6 villages and sub-districts in Moyo Utara District, namely Baru Tahan Village, Kukin Village, Penyaring Village, Pungkit Village, Sebewe Village and Songkar Village. The problem experienced by horse farmers in Penyaring Village is the less than optimal management of the use of wild horse milk which causes relatively low income. So far, the horse milk produced has not been optimal in terms of management utilization, farmers are only limited to milking and selling at a relatively cheap price or selling it only for daily needs so that it does not have a sustainable impact in terms of sales value. The purpose of making milk candy is to increase the economic value of milk and the income of farmers. In addition, the service activity of making milk candy can also establish cooperation between the University and horse breeders and the farming community and increase the production of milk candy, be able to process milk into processed products that last a long time, and to add to the taste of milk.